Rola i proces szkolenia pracowników w systemach produkcyjnych - Janiak-Rejno, Iwona; Chomątowska, Barbara (The Role an the Training Process of Employees in Production Systems, 2008)
Recently the role and the meaning of employees training have grown in production systems. Key factors influencing this state are changes in the external and internal environment of these systems (engineering, technological, social, economic changes) and additionally the necessity for flexible reaction towards these. Proper level of productive staff, both managers and workers, decides about success and the competitiveness of modern productive enterprises. The important role in this area has employees training. The aim of this article is to present the role and the training process of employees in production systems. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 47-56